2011 Digital Signal Processing and Signal Processing Education Meeting (DSP/SPE) 2011
DOI: 10.1109/dsp-spe.2011.5739197
|View full text |Cite
|
Sign up to set email alerts
|

Speech enhancement by combination of transient emphasis and noise cancelation

Abstract: This paper evaluates the effectiveness of combining speech modification techniques that enhance transition components with active noise cancellation to improve the intelligibility of speech in noise. Two speech modification techniques were considered. One is based on wavelet-packet analysis, and the second uses a fixed filter, derived from timefrequency analysis, that emphasizes high frequencies.Active noise cancellation was provided by Bose noisecancelling headphones. The test noise was real, generated by a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…6.2.7. Boost transients [247] found transient-boosting methods can improve intelligibility of speech in noise (recordings of an aircraft auxiliary power unit) presented at various SNRs from -30 dB to -10 dB, and that gains were still seen when combining this with active noise-cancelling headphones. Although the best-performing method was inspired by a dynamic timevarying filter approach, in order to obtain real-time performance this was approximated as a simple fixed filter, which amounts to attenuation below 700Hz and mid-and high-frequency boosting.…”
Section: Increase/decrease Fmentioning
confidence: 99%
See 1 more Smart Citation
“…6.2.7. Boost transients [247] found transient-boosting methods can improve intelligibility of speech in noise (recordings of an aircraft auxiliary power unit) presented at various SNRs from -30 dB to -10 dB, and that gains were still seen when combining this with active noise-cancelling headphones. Although the best-performing method was inspired by a dynamic timevarying filter approach, in order to obtain real-time performance this was approximated as a simple fixed filter, which amounts to attenuation below 700Hz and mid-and high-frequency boosting.…”
Section: Increase/decrease Fmentioning
confidence: 99%
“…Distortions introduced by that method may have counteracted the benefits of transient boosting. From the results available in [247] and from simple spectral shaping, it is not possible to separate out the effects of a general high-frequency boost from specific localised transient boosting. [322] also found that increasing the intensity of transients relative to steady-state regions increased intelligibility.…”
Section: Increase/decrease Fmentioning
confidence: 99%
“…In speech enhancement systems (SES), a similar approach is active noise cancellation, in which the noise signal is directly measured and then removed form the noisy speech signal. Algorithm noise cancellation requires a separate microphone to record the noise alone, it is successfully implemented to improve speech intelligibility and is now widely availably commercially [1]- [3]. A conventional approach in SES system is to use FIR filters as adaptive controllers where the filter coefficients are adjusted according to the least mean square (LMS) algorithm to minimize errors between output of the filters and the desired response.…”
Section: Introductionmentioning
confidence: 99%